An hybrid ACO-based approach for media service composition in video surveillance platform - Hossain, M. Shamim; Hassan, Mohammad Mehedi (2013 IEEE International Conference on Multimedia and Expo Workshops (ICMEW), 2013)
Distributed video surveillance environments need dynamic service composition capability in order to adapt to varying video surveillance access needs in security industry such as banks, airports, and other public places. To this end, this paper presents a hybrid-ACO-based service composition approach for the efficient delivery of media service to surveillance users. The proposed hybrid ACO-based algorithm is a part of AntNet and a part of Genetic algorithm, which make use of the advantages of both algorithms. Experiment results show that the proposed approach is efficient, has promising performance in selecting media service composition path based on some QoS metric.